The Influence of Local Own-Source Revenue (PAD), Economic Growth, Capital Expenditure on Fiscal Stress in Central Sulawesi in 2018-2023 - Amal, Husaeva; Sading, Yunus; Yunus, Rita; Yunus, Santi; Rafika, Ika (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
This study aims to analyze the influence of Local Own-Source Revenue (PAD), Gross Regional Domestic Product (GRDP), and Capital Expenditure on fiscal stress in 13 regencies/municipalities in Central Sulawesi Province during the period 2018–2022. The approach used is quantitative with panel data, which is a combination of time series and cross-sectional data sourced from the Central Bureau of Statistics (BPS). Analysis was conducted using panel data regression models with EViews software. The selection of the best model was done through a series of statistical tests: Chow Test, Hausman Test, and Lagrange Multiplier, which showed that the Random Effect model was the most appropriate. The results show that simultaneously, PAD, GRDP, and Capital Expenditure have a significant effect on fiscal stress. Partially, PAD and Capital Expenditure have positive and significant effects, while GRDP does not show a significant effect. The coefficient of determination indicates that most variations in fiscal stress can be explained by these three variables. These findings confirm that fiscal stress results from complex interactions of various economic factors, with PAD and Capital Expenditure as the main factors. The implications of this study highlight the importance of strengthening regional fiscal independence through PAD optimization, efficient Capital Expenditure management, and efforts to achieve sustainable economic growth.